FEM based thermal and mechanical analysis of comparative study of TIG and A-TIG welding on P91 steel - M. Zubairuddin; M. Vasudevan; P. K. Das; Mohammad Mukhtar Alam; K. Suresh Kumar; S. Prabhakar (Scientific Reports)
Abstract Present research deals with the thermo-mechanical analysis of the butt joint plate and weld pool characteristics of the bead on plates fabricated using A-TIG and conventional TIG process. A square butt joint was welded using P91 steel of 4 mm thickness plates, employing in-house developed oxide flux. Thermal cycles induced during the welding was recorded with thermocouple, and residual stress produced in both plates was measured using the XRD method. It is observed that A-TIG produces less detrimental effects than the conventional TIG. Concentrated heat intensity is observed during the A-TIG with the narrow and deep penetration depth dispersed with lesser heat to base metal than the TIG welded joint. Comparison of bead on plate showed that FZ and HAZ increase to 10% and 34% more widely in the TIG welding process. The maximum stress value in the A-TIG welding process reached up to 471 MPa near the weld bead, whereas in the TIG welding, it was 509 MPa with 8% reduction in stress value. Reduction in distortion is also observed in the case of A-TIG, with a 36% reduction in values. Distortion in the weld plate is also compared with predicted results. FEM-based simulation is performed for both processes using the SYSWELD. Combined double ellipsoidal with conical heat source model was used for A-TIG and double ellipsoidal model was used for conventional TIG welding. Based on the comparison of the results, it can be concluded that the predicted results are approximately near to experimental measured values for thermal and mechanical results. It is observed that A-TIG plate induced less distortion and stress than the conventional TIG process.